Spectral cross-cumulants for multicolor super-resolved SOFI imaging - K. S. Grußmayer (Nature Portfolio, 2020)
Here, the authors generalize cumulant analysis by extending it into the spectral domain to allow multicolour super-resolution optical fluctuation imaging. The simultaneous acquisition of two spectral channels followed by spectral cross-cumulant analysis and unmixing allows denser spectral and spatial sampling of the super-resolved image.